The Activeness of Interactions in Learning Management System and Students' Performances - M. Hisyam, M. Hashim; Yusup, Hashim; Ahmad, Esa (David Publishing, 2011)
Interactions in LMS (learning management system) are needs in the implementation of online learning as a method for teaching and learning. A good performance in learning is a learner’s dream. The purpose of this research is to identify the correlations between interactions and students performances. This research is worth to be studied due to several problems for implementation of online learning in the organisations, such as the lack of LMS tools usage amongst the lecturers and students in Higher Institution Education Organisation. Pearson Crostab descriptive analysis has been used to explain correlation between interactions and students performances. The Pearson Crostab descriptive analysis also could show the significant correlation between activeness interations and students performances. This finding also explains that even though LMS had been implemented and used, it still needs several components in order to help the teaching and learning process as well as improve the students performances. Keywords: interactions, students performances, Pearson Crostab, LMS (learning management system)